Energy Generation Through Vibration using Piezoelectric with Smart Monitoring System - Razali, Zul Adib Izzuddin; Salimin, Suriana (Evolution in Electrical and Electronic Engineering, 2022)
Nowadays, electrical energy is crucial and becoming more in demand. Many energy resources have been mismanaged and depleted. A new method of generating power utilising a human population has been developed to produce the eco-friendly sources of electrical energy. The vibration generated between the surface of the roadway or walkway produced from vehicles vibrations and footstep are wasted. Electrical energy may be created and the need met by reusing this lost energy. A piezoelectric material is the type of transducer used to detect vibrations. The kinetic energy is converted into electrical energy by this sensor. The purpose of this research is to design the piezoelectric tile as an independent power source utilising the vibration into electrical energy. When the pressure from a footstep or vehicles are delivered to a piezoelectric material, the stress or force is converted into electrical energy. The piezoelectric materials then put on a wooden tile as a model for a piezoelectric tile to apply pressure to the piezoelectric materials. The output voltage then will be stored in the rechargeable battery as a storage device. This tile can be used in a crowded location like on a walkway, roadway or on workout equipment. This proposed design is combined with the smart monitoring system to monitor the battery voltage while the piezoelectric is used as a charging device.